Friedrich II. von Preussens De la littérature allemande. Zum historischen Standort des Aufsatzes und zu seiner Übersetzung im Spanischen. Literarische und kulturhistorische Aspekte - Rohland de Langbehn, Regula (Revista de Filología Alemana, 2005)
The concept of literature used by Frederick II, King of Prussia, in his essay on German Literature is reexamined in this paper. We propose as one of the instigators for writing the original essay Friedrich Melchior von Grimm, who wrote two articles on German Literature in 1750, years before his famous Correspondence Littéraire. The concept of literature as used in the essay is a traditional concept, much broader than we use it nowadays, for it refers to all written products, not to literature as “belles lettres”. This means that some suspicacies which came about among the German authors of the time and which have still been discussed during the XXth Century are based on a faulty understanding of the author’s meaning. This misunderstanding does not extend to Spain, since the Prussian monarchs solid fame abroad and the illuminist interests in Spain led to reception, in the first instance, of the essays pedagogical aspects and formative intentions. W discuss also a review which was published in the Correo Literario in 1781 and its incidence in the Spanish translation, which was published anonymously in 1787.